Penghentian Prematur atas Prosedur Audit - Suryanita Weningtyas; Doddy Setiawan; Hanung Triatmoko (The Indonesian Journal of Accounting Research, 2013)
Premature sign off of audit procedure is one form of Reduced Audit Quality / RAQ behaviors. This act refers to falsely signing off a required audit step, which is not covered by other steps, without completing the work or noting the omisson of the procedures. However, auditor dares to express an opinion based on those procedures. An auditor can  make a wrong opinion on the financial statement if he conducts such act. As a result, litigation risk faced by an auditor will increase because of issuing a wrong opinion.  The objectives of this research are : first,  to know the sequence of audit procedures which most are often signed off and second, to test the effect of time pressure, audit risk, materiality, review procedure and quality control on premature sign off of audit procedure.The result of this research indicates that there is a priority sequence of discontinued audit procedure in time pressure conditions. The audit procedure which is often omitted is understanding business’s client and the audit procedure which is seldom omitted is physical examination. The logistic regression shows that time pressure, audit risk, materiality, review procedure and quality control have an effect on prematurly signed off audit procedure.